Accounting and Costing at the Broken Hill Associated Smelters Proprietary Ltd. Works, Port Pirie (The Australasian Institute of Mining and Metallurgy, 1922)
As this paper is being written primarily for perusal by milling workers, metallurgists and engineers, an attempt will be made to avoid the use of accounting technicalities. Its scope will be confined to a description of the methods employed in the collection of basic information for use in timekeeping, costing, and the compilation of statistics.TIMEKEEPINGEvery applicant for work is asked to furnish the following information, which is collected on a card (size 6 in. x 4 in.)...